The mannose 6-phosphate receptor targeted with porphyrin-based periodic mesoporous organosilica nanoparticles for rhabdomyosarcoma theranostics. (29th May 2020) - Daurat, Morgane; Nguyen, Christophe; Dominguez Gil, Sofia; Sol, Vincent; Chaleix, Vincent; Charnay, Clarence; Raehm, Laurence; El Cheikh, Khaled; Morère, Alain; Bernasconi, Michele; Timpanaro, Andrea; Garcia, Marcel; et al.
Abstract : Periodic mesoporous organosilica nanoparticles targeted to the mannose 6-phosphate receptor for rhabdomyosarcoma photodynamic therapy using a pulsed laser. Abstract : Porphyrin-based periodic mesoporous organosilica nanoparticles (PMO) synthesized from a large functional octatriethoxysilylated porphyrin precursor and allowing two-photon excitation photodynamic therapy (TPE-PDT) and NIR imaging were synthesized. These PMO were grafted with polyethylene glycol (PEG) moieties and an analogue of mannose 6-phosphate functionalized at the anomeric position (AMFA). AMFAs are known to efficiently target mannose 6-phosphate receptors (M6PRs) which are over-expressed in various cancers. Here, we demonstrated for the first time that M6PRs were over-expressed in rhabdomyosarcoma (RMS) cells and could be efficiently targeted with PMO–AMFA allowing TPE imaging and TPE-PDT of RMS cells. The comparison with healthy myoblasts demonstrated an absence of biological effects, suggesting a cancer cell specificity in the biomedical action observed.